Basic Concept of Positivism in the Development of Legal Studies - Gadjong, Agussalim Andi (UI Scholars Hub, 2011)
Legal norms governing a social system are known as the legal system, which function as guidelines for the creation of rules for community members. A legal system comprises norms (principles) serving as guidance (reference), either individually or in groups, which include command (compulsion) and restrictions (regulation) as well as sanctions. Command and restrictions are construed as the materialization of the agreement made in regulating interactions, which can be used as comprehensive guidelines in the social system. Whereas sanctions are intended as retribution (punishment) for any person (group) who fails to abide by (comply with) the rules. Retributions as the consequences of the agreement on a legal system as well as sanctions provided for in the legal system constitute psychological motivation for taking or refraining from taking action.